Detailed kinetic model of oxidation and combustion of n-heptane using an automatic generation of mechanisms - Yuswan Muharam (Jurnal Teknik Kimia Indonesia, 2006)
There is continued interest in developing a better understanding of the oxidation and combustion of large hydrocarbons, which are good representative for practical fuels used in automotive engines for a wide range of operating conditions. This interest is motivated by the need to improve the efficiency and performance of currently operating combustion systems, the fuel economy, and the need to reduce pollutant emission. Normal-heptane is one of these hydrocarbons.  In this work a detailed chemical kinetic model for the oxidation and combustion of n-heptane has been automatically developed using a computer code called MOLEC. The model consisting of 486 species taking part in 2008 elementary reactions was used to reproduce experimental results of n-heptane oxidation in shock tubes. The experimental study of the ignition delay times of n-heptane/O2/Ar behind a reflected shock wave for equivalence ratios of 0.5-4.0 in a temperature range of 1300 K- 2000 K can be reproduced well by the model. Experimentally derived and numerically predicted ignition delays of n-heptane/air mixtures in a high-pressure shock tube in a wide range of temperatures, pressures, and equivalence ratios agree very well. Sensitivity analyses were performed for shock tube environment in an attempt to identify the most important reactions under the relevant conditions of study.Keywords: Modelling, Oxidation, Combustion, Kinetics, Fuels AbstrakDewasa ini di dunia muncul minat yang berkelanjutan dalam mengembangkan proses oksidasi dan pembakaran hidrokarbon panjang, yang merupakan representatif yang meyakinkan bagi  bahan bakar praktis yang digunakan di dalam mesin kendaraan bermotor dalam rentang kondisi operasi yang Iebar. Keminatan ini dipicu oleh keinginan untuk meningkatkan efisiensi dan kinerja sistem pembakaran yang digunakan saat ini, ekonomi bahan bakar serta kebutuhan untuk mengurangi emisi polutan. Normal-heptane merupakan salah satu hidrokarbon ini. Di dalam riset ini sebuah model kinetika kimia detail untuk oksidasi dan pembakaran n-heptana dikembangkan secara otomatis dengan menggunakan sebuah kode komputer yang disebut MOLEC. Model yang terdiri dari 486 spesies yang berperan serta di dalam 2008 reaksi elementer digunakan untuk mereproduksi hasil hasil eksperimen oksidasi n-heptana di dalam shock tubes. Has il eksperimen ignition delay times n heptana/ O2/Ar di dalam shock tube untuk rasio ekuivalensi 0,5-4,0 pada rentang temperatur 1300 K- 2000 K dapat direproduksi dengan baik oleh model. Ignition delay campuran n-heptanal udara hasil eksperimen dan hasil perhitungan numeris di dalam shock tube bertekanan tinggi dalam rentang temperatur, tekanan, dan rasio ekuivalensi yang luas sangat bersesuaian satu sama lain. Analisis sensitivitas dilakukan dalam upaya mengidentifkasi reaksi-reaksi yang paling penting di dalam kondisi kajian yang relevan.Kata Kunci: Modeling, Oksidasi. Pembakaran, Kinetika, Bahan Bakar